Sosialisasi Pemanfaatan Tanaman Obat Keluarga (TOGA) Sebagai Pengobatan Herbal Bagi Masyarakat Kalurahan Terbah - Muhamad; Arsyita Hayatun Nisa; Sekar Syahriza; Yogi Tri Sumarno; Rafa Ahamada Wijaya (Direktorat Pengabdian kepada Masyarakat, 2026)
The utilization of Physic Garden (TOGA) has not been implemented optimally because the level of understanding andknowledge of the community about the types and benefits of medicinal plants is still low so that it has not been prioritized for disease prevention and treatment. This awareness-raising program can be used as a source of knowledge for the community to maximize the utilization of TOGA for herbal medicine, to add more the value of medicinal plants, and to improve the public health in producing a herbal medicine product in Terbah village. The implementation of the methodology encompasses observation, presentation of the material, discussion, feedback session as evaluation, and giving examples of TOGA seeds. According to the result of the program, it shows that there is a lack of knowledge and understanding about the utilization of natural resources as herbal medicine. Thus, hopefully there will be an increase in community knowledge about TOGA in order to increase people’s understanding and awareness of the importance of health for themselves and family members that can be obtained from TOGA planted in the yard.